2014
DOI: 10.1016/j.anihpc.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Hardy inequalities on Riemannian manifolds and applications

Abstract: We prove a simple sufficient criteria to obtain some Hardy inequalities on Rie-\ud mannian manifolds related to quasilinear second-order differential operator ∆p u :=\ud div | u|p−2 u . Namely, if ρ is a nonnegative weight such that −∆p ρ ≥ 0, then\ud the Hardy inequality\ud c M\ud |u|p\ud | ρ|p dvg ≤\ud ρp\ud | u|p dvg ,\ud ∞\ud u ∈ C0 (M ).\ud M\ud holds. We show concrete examples specializing the function ρ.\ud Our approach allows to obtain a characterization of p-hyperbolic manifolds as\ud well as other in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 37 publications
0
69
0
Order By: Relevance
“…In the section, we study the Hardy inequalities for p-sub/superharmonic functions in the Finsler setting. Inspired by D'Ambrosio and Dipierro [13], we have the following result. (2) Additionally suppose F p (∇ρ) ρ p−α , ρ α ∈ L 1 loc (Ω) if α > p. Then we have the following weighted Hardy inequality…”
Section: 2mentioning
confidence: 88%
See 1 more Smart Citation
“…In the section, we study the Hardy inequalities for p-sub/superharmonic functions in the Finsler setting. Inspired by D'Ambrosio and Dipierro [13], we have the following result. (2) Additionally suppose F p (∇ρ) ρ p−α , ρ α ∈ L 1 loc (Ω) if α > p. Then we have the following weighted Hardy inequality…”
Section: 2mentioning
confidence: 88%
“…We also have a logarithmic Hardy inequality. [12,13,25]). Moreover, Theorem 1.3 can be generalized to the irreversible case.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there has been growing interest in establishing Hardy and Rellich type inequalities on Riemannian manifolds, e.g. , , , , , –, , and the references therein. In an interesting paper, Carron developed a general principle to derive weighted L 2 Hardy type inequalities on complete Riemannian manifolds.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, D'Ambrosio and Dipierro showed that if ρ is a nonnegative weight function such that (p1α)divρp2ρ0then the following Hardy type inequality Mρα|ϕ|pdV()|p1α|ppMραp|ρ|p||ϕpdVholds for all ϕC0M, p>1 and αR.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors consider generalized versions of the inequalities with remainder terms [1,4,28] as well as those expressed in Orlicz setting [15,17,44,46]. Recently, Hardy-type inequalities are investigated also on Riemannian manifolds [26].…”
mentioning
confidence: 99%